A common fixed point theorem on fuzzy metric space - Srinivas, V; Reddy, BVB; Rao, R Umamaheshwar (Kathmandu University Journal of Science, Engineering and Technology, 2013)
The purpose of this paper is to prove a common fixed point theorem in a fuzzy metric space using the concept of weakly compatible mappings. Kathmandu University Journal of Science, Engineering and Technology Vol. 8, No. II, December, 2012, 77-82 DOI: http://dx.doi.org/10.3126/kuset.v8i2.7328